Critical Thinking and Productive Language Skills: A Literature-Based Approach - Sagimin, Eka Margianti (IJLHE: International Journal of Language, Humanities, and Education, 2025)
In the evolving landscape of higher education, the development of critical thinking (CT) has emerged as a fundamental educational objective, particularly in foreign language instruction. While considerable attention has been given to integrating CT into receptive language activities such as reading and listening, productive skills—namely speaking and writing—remain underexplored in this regard. This article investigates the effectiveness of targeted instructional strategies and technologies designed to foster CT during productive language learning tasks. Drawing on a structured framework encompassing mental operations and cognitive phases (activation, comprehension, and reflection), this study identifies and systematizes pedagogical methods that simultaneously develop linguistic proficiency and CT competencies. These include essay writing, structured discussion, conceptual mapping, clustering, annotation, forecasting, and project-based learning, all aligned with higher-order cognitive functions such as analysis, synthesis, evaluation, and decision-making. The study concludes that intentional integration of CT-promoting strategies into productive language skills instruction significantly enhances learner engagement, autonomy, and cognitive agility. The findings underscore the need for continued pedagogical innovation and offer practical implications for language educators aiming to bridge linguistic and critical competencies in university settings.